Perlindungan Hukum Lahan Pertanian Pangan Berkelanjutan di Wilayah Desa Babirik - Sugiyanto, Dedi; Tsani, Miftah Ulumudin; Kusumah, Athaya Salsabila Farendra; Ramadhana, Muhammad (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2024)
The existence of the State of Indonesia as an Agrarian State has been mandated in the Constitution of the Republic of Indonesia which gives the State the responsibility to guarantee the right to food as the right to food security and sovereignty. The State's obligation to maintain food security is faced with the challenge of meeting increasing food needs, and especially due to the increasingly rapid increase in population, it is necessary to make efforts to prevent land degradation, with the enactment of Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land. In the Explanation of Law Number 41 of 2009 it is stated that the conversion of agricultural land is a threat to the achievement of food security and sovereignty. The purpose of this PKM is to provide knowledge, understanding and legal awareness to the community about the legal aspects of Sustainable Food Agricultural Land Protection. The method used is the Presentation Method with the concept of partnering with the Babirik village office and presenting several community leaders interactively with the community to understand the importance of legal protection for Sustainable Food Agricultural Land. The results of the implementation of the activity are that the community understands the legal basis for the Protection of Sustainable Food Agricultural Land in the Babirik Village area, namely Law Number 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land and Banjar Regency Regional Regulation Number 9 of 2012 concerning the Protection of Sustainable Food Agricultural Land which stipulates agricultural land that must be protected, including monitoring mechanisms and sanctions for violations. The conclusion of this Activity has succeeded in helping the community understand the various incentives available to support agricultural activities, as well as the importance of complying with provisions regarding land conversion to prevent violations of the law. Eksistensi Negara Indonesia sebagai Negara Agraris telah dimanatkan dalam Konstitusi Negara Republik Indonesia yang memberikan tanggung jawab kepada Negara untuk menjamin hak atas pangan sebagai hak ketahanan dan kedaulatan pangan. Kewajiban Negara dalam menjaga ketahanan pangan dihadapkan pada tantangan pemenuhan kebutuhan pangan yang semakin meningkat, dan terutama disebabkan oleh peningkatan populasi yang semakin cepat, maka perlu dilakukan upaya pencegahan terjadinya degradasi lahan, dengan ditetapkannya Undang-Undang Nomor 41 Tahun 2009 tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan. Dalam Penjelasan Atas Undang-Undang Nomor 41 Tahun 2009 disebutkan bahwa alih fungsi lahan pertanian merupakan ancaman terhadap pencapaian ketahanan dan kedaulatan pangan. Tujuan dari PKM ini untuk memberikan pengetahuan, pemahaman dan kesadaran hukum kepada masyarakat tentang aspek hukum Perlindungan Lahan Pertanian Pangan Berkelanjutan. Metode yang digunakan adalah Metode Presentasi dengan konsep bermitra dengan kantor desa Babirik dan menghadirkan beberapa tokoh masyarakat secara interaktif bersama masyarakat untuk memahami pentingnya perlindungan hukum atas Lahan Pertanian Pangan Berkelanjutan. Hasil pelaksanaan kegiatan yaitu masyarakat memahami dasar hukum Perlindungan Lahan Pertanian Pangan Berkelanjutan di wilayah Desa Babirik yaitu Undang-Undang Nomor 41 Tahun 2009 tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan dan Peraturan Daerah Kabupaten Banjar Nomor 9 Tahun 2012 tentang Perlindungan Lahan Pertanian Pangan Berkelanjutan yang menetapkan lahan pertanian yang harus dilindungi, termasuk mekanisme pengawasan dan sanksi bagi pelanggaran. Kesimpulan dari Kegiatan ini telah berhasil membantu masyarakat memahami berbagai insentif yang tersedia untuk mendukung kegiatan pertanian, serta pentingnya mematuhi ketentuan mengenai alih fungsi lahan untuk mencegah pelanggaran hukum